Regarding "I Am Not Captain Dunsel!" (Fall 2009) - Susanne J. Redalje (Issues in Science and Technology Librarianship, 2010)
A letter to the editor is presented in response to the article of Steven Bell which appeared in the October 2: 2009 issue of "LJ Newswire."